The role of gut microbiota in depression: an analysis of the gut-brain axis - Irum, Natasha; Afzal, Tayyeba; Faraz, Muhammad Hamid; Aslam, Zeeshan; Rasheed, Faisal (Frontiers in Behavioral Neuroscience, 2023)
The gut-brain axis is a communication pathway that allows a two-way exchange of information between the microbiota of the gastrointestinal tract and the nervous system of humans. The vagus nerve, which is responsible for facilitating communication, provides support for this axis. The gut-brain axis is currently the subject of research, but studies into the diversity and stratification of the gut microbiota are just getting started. Researchers have discovered several positive trends by analyzing numerous studies examining the gut microbiota's impact on the effectiveness of SSRIs. It is common knowledge that a specific group of measurable, microbial markers has been recognized as being present in the feces of individuals suffering from depression. Specific bacterial species are a common denominator among therapeutic bacteria used to treat depression. It can also play a role in determining the severity of disease progression. Evidence that selective serotonin reuptake inhibitors (SSRIs) rely on the vagus nerve to exert their therapeutic effects has provided further support for the importance of the vagus nerve in the gut-brain axis, which is necessary for beneficial changes in the gut microbiota. This review will analyze the research linking gut microbiota to depression.